Controle da dinâmica caótica do oscilador de morse forçado - Ramos, Tárcius Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In this work, the dissociation dynamics of heteronuclear diatomic molecules is investigated by means of the classical driven Morse oscillator. The interaction of the molecule and the laser field is represented through the product of the molecule dipole function and the electric field of the laser. This interaction may lead to the breaking of the chemical bound, that is, to the dissociation of the molecule. The work was developed in two parts. In the first part, we studied the dissociation as a function of the range of the permanent dipole. In the second part, we maximized the dissociation probability manipulating the parameters of the external field. We have observed that the dissociation can be controlled by means of variations of parameters associated with the range of the permanent dipole

Neste trabalho, a dinâmica de dissociação de moléculas diatômicas heteronucleares é investigada através do oscilador de Morse forçado clássico. A interação da molécula com um laser é representada através do produto da função momento de dipolo da molécula com o campo elétrico do laser. Essa interação pode levar a quebra da ligação química, ou seja, à dissociação molecular. O trabalho foi realizado em duas etapas. Na primeira etapa, estudamos a dissociação em função do alcance do momento de dipolo permanente. Na segunda etapa, maximizamos a probabilidade de dissociação através do controle dos parâmetros do campo externo. Observamos que a dissociação pode ser controlada por meio de variações dos parâmetros associados ao alcance do dipolo permanente
Keywords: Dinâmica; Dissociação; Físico-química; Moleculas